PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, DAN KOMITE AUDIT TERHADAP INCOME SMOOTHING - Clarissa Nathania; Vidyarto Nugroho (Jurnal Paradigma Akuntansi, 2023)
This study has a purpose, namely to empirically examine the influence of firm size,profitability, leverage, and audit committee towards income smoothing inmanufacturing companies listed in Indonesia Stock Exchange from 2017-2019. Thisstudy used 75 samples from manufacturing companies that have been selected usingpurposive sampling method with total 225 data for three years. The data used aresecondary data in the form of financial statements. This research used econometricviews (EViews) version 11 software to process the data. The result of research showsthat firm size, profitability, and leverage have negative significant influence towardsincome smoothing, meanwhile audit committee has no significant influence towardsincome smoothing. The implication of this research is the need for transparency offinancial reports regarding profit and debt, as well as an increase in the role of theaudit committee to reduce income smoothing practices at various firm sizes.